Statistical Modeling for the Effects of Vegetative Growth on Power Distribution System Reliability - Pan, Juming (Frontiers in Applied Mathematics and Statistics, 2021)
The purpose of this paper is to examine the effects of vegetative growth on the reliability of electric power distribution system under normal (storm exclusion) operating conditions, and to determine an effective vegetation maintenance schedule. Generalized statistical linear regression models, including Poisson, Negative Binomial, zero-inflated, and their mixed model variants are developed, and are applied into a 5-year outage data along with vegetation maintenance history from a power company in Midwestern United States. The results quantify a significant impact of vegetation on electric power system outages, and suggest an optimal cycle length of every 6 years. The study should be useful for power companies in predicting vegetation‐related outages and setting vegetative maintenance frequencies.